The efficiency of E-KON system in the design and development process of the Shurtan gas condensate field - B. Kh. Bekov; O. A. Khujaev (Наука. Инновации. Технологии, 2025)
The article analyzes the efficiency of E-KON system in the design and development process of the Shurtan gas condensate field. The study is conducted within the framework of the strategic program Digital Uzbekistan-2030 and aims to demonstrate the advantages of digital technologies in the oil and gas industry. The article highlights a number of key aspects of the E-KON system, including the optimization of technological well operation modes, increased gas production volumes, and measures to prevent well flooding. One such measure is the removal of formation water through blowouts, which ensures more stable well operation and minimizes the risks of productivity loss. The possibilities of integrating the E-KON system with databases have been considered, which contributes to improved data management and allows for the prompt monitoring and analysis of operational performance. This approach ensures a reduction in operational costs, enables flexible regulation of production processes, facilitates informed management decisions based on accurate data, and stores all data in one place. The analysis of the practical results of using the E-KON system showed positive effects, including an increase in gas production volumes and overall optimization of operations. The data presented confirm that the E-KON system not only contributes to improved productivity but also enhances the overall effectiveness of field management and ensures the sustainable development of the gas condensate field. The article also emphasizes the importance of implementing advanced information technologies to enhance process transparency, improve monitoring, and facilitate operational decision-making, which helps reduce risks and increase project profitability.